2020
DOI: 10.1002/pat.5202
|View full text |Cite
|
Sign up to set email alerts
|

Tuning polylactic acid scaffolds for tissue engineering purposes by incorporating graphene oxide‐chitosan nano‐hybrids

Abstract: The main goal of this study was to take an effective approach to promote polylactic acid (PLA) bio‐applications. In this regard, graphene oxide (GO) and spherical structure of GO‐chitosan nano‐hybrids (GO‐CS) were successfully synthesized and characterized using transmission electron microscopy, atomic force microscopy, Fourier‐transform infrared, UV–Vis, and elemental analyses. Thereafter, PLA scaffolds containing 1 wt% and 2 wt% of synthesized nanomaterials were fabricated through the solvent casting/particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 67 publications
1
4
0
Order By: Relevance
“…Coating GO, just on the surface, diminished the risk of toxicity of GO as it has a low concentration in the structure, according to the studies that answered concerns about its potential toxicity and possible residue in vivo. [ 42,45 ] Also, as reported by other studies, [ 46,47 ] PLA–GO scaffolds demonstrate higher hydrophilicity than PLA scaffolds, promoting cell adhesion and viability, and this study agrees with those findings.…”
Section: Discussionsupporting
confidence: 92%
“…Coating GO, just on the surface, diminished the risk of toxicity of GO as it has a low concentration in the structure, according to the studies that answered concerns about its potential toxicity and possible residue in vivo. [ 42,45 ] Also, as reported by other studies, [ 46,47 ] PLA–GO scaffolds demonstrate higher hydrophilicity than PLA scaffolds, promoting cell adhesion and viability, and this study agrees with those findings.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, more ambivalent findings are described in the literature for PLA. For example, Li et al [ 81 ] and Silva et al [ 82 ] observed good biocompatibility, while Lee et al [ 80 ] reported inflammatory responses to PLA scaffolds and Majidi et al [ 83 ] observed a reduction in viability of L929 fibroblast cells by almost 50% after 72 h, although they attributed this to reduced cell attachment and not a toxic effect. In agreement with the results of Majidi et al, we observed a decrease in cell viability for PLA, which can also be attributed to either decreased cell adhesion or a toxic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Chitosan functionalization also facilitates the incorporation of the scaffolds in the body and the interaction with the extracellular matrix [ 177 ]. Several experiments have observed that collagen type I secretion supported the cell adherence processes when the patches loaded with the stem cells of the stem cell-derived cardiomyocytes were used to replace the necrotic cardiomyocytes.…”
Section: Role Of the Chitosan Scaffolds In Myocardial Tissue Regenera...mentioning
confidence: 99%